Molecular regulation of ornithine decarboxylase (ODC) enzyme in mammalian cells - ISABELA ANJANI,; RAYMOND R. TJANDRAWINATA, (International Journal of Pharma and Bio Sciences, 2017)
Polyamines (putrescine, spermidine and spermine) are ubiquitous low molecular weight amines that are positively charged under physiological conditions. Homeostatic control of intracellular polyamines levels is achieved by regulating the synthesis, catabolism and transport of these molecules. Polyamines are involved in the regulation of diverse range of vital cellular processes in both eukaryotic and prokaryotic cells, including cell proliferation, signal transduction and membrane stabilization. Putrescine, spermine and spermidine, universally occurring in mammalian cells, are involved in a wide array of processes, ranging from triggering growth and proliferation to protecting against stress. Ornithine decarboxylase (ODC) initiates the polyamine biosynthetic pathway by producing putrescine. The amount of ODC is altered in response to many growth factors, oncogenes and tumor promoters and to changes in polyamine levels. This review describes key factors that contribute to the regulation of ODC levels and activities, which can occur at the levels of transcription, translation and protein turnover.